MATO PRETO ALKALINE-CARBONATITE COMPLEX: GEOCHEMISTRY AND ISOTOPE (O-C, Sr-Nd) CONSTRAINS - Comin-Chiaramonti, P.; Gomes, C. B.; Ruberti, E.; Antonini, P.; Castorina, F.; Censi, P. (Geochimica Brasiliensis, 2011)